The influence of strategy formation capability on firm’s value creation: An empirical review - Nik Abdullah, Nik Herda; Said, Jamaliah (2015)
Value creation analysis is a critical element yet often disregarded by the financial management as one of the important elements in an organization, including Malaysian Government Linked Companies (GLCs).The creation of use value is essential for sustaining the firm.Without this component, firms would have no added value and there would be no reason for firms to exist.These use values are recognized when someone perceives the resources or products of a firm as valuable and people might perceive values differently.GLCs hold a main profit-making objective, in which the Malaysian Government possesses a direct controlling stake and serves as the backbone of the Malaysian economy.By possessing the value creation element, GLCs are expected to create sustainability, have a competitive advantage and produce a better business performance in order to enhance the interest of shareholders, creditors, employees, suppliers, customers, governments and communities. Prior studies have shown that value creation can be created through strategy formation. Strategy formation is the core of strategic management and is related to the effectiveness of the firm’s strategy, which leads to better performance.An effective strategy formation capability is valuable because it enables the firm to create strategies that increase its effectiveness or efficiency and when it matches the firm’s environment that eventually leads to a competitive advantage. This paper tried to ascertain the influence of strategy formation capability on value creation, which then improves a firm’s reputation, product differentiation and process innovation in GLCs.The strategy formation capability tends to provide an empirical review that enables the top management and policy makers to review the strategy formation capability in order to create the firm’s value, achieve sustainable growth and improve GLCs competitiveness in the global market.